I am the book : poems - Yayo; Hopkins, Lee Bennett (New York : Holiday House, 2011)
An illustrated collection of poems that celebrates reading, featuring selections by Karla Kuskin, Jill Corcoran, Jane Yolen, and others.
3.4
K-3
K-3
Keywords: Books and reading -- Juvenile poetry; Books -- Juvenile poetry; Children's poetry, American; Books and reading -- Poetry; Books -- Poetry; Books and reading -- Poetry; Books -- Poetry; Picture books for children